THEORETICAL AND METHODOLOGICAL PRINCIPLES OF TRAINING FUTURE VOCATIONAL TEACHERS TO USE LEARNING MANAGEMENT SYSTEMS - STECHYSHYN , Ihor (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2026)
Modern trends in the development of pedagogical education necessitate the integration of new approaches to managing the educational process to ensure its quality, guarantee compliance with new standards and international requirements, and increase the competitive advantages of the institution. The purpose of the article is to analyze the theoretical and methodological foundations of training future teachers of vocational training to use educational process management systems. The study identifies key vectors of transformation of pedagogical education, in particular, the introduction of forms of distance and blended learning, integration of digital tools and artificial intelligence, which is reflected in learning management systems. The specifics of the Moodle learning management system are analyzed, the main advantages of which are accessibility, flexibility and adaptability, versatility, a wide range of practical tools, and extensibility. The main methodological approaches to learning management systems are considered, including systemic, person-oriented, competency-based, integrated, and innovative approaches, which determine the basic theoretical provisions and principles on the basis of which effective management of the educational process using technologies is built. The challenges of modern education management are determined, including uneven resource provision, insufficient staff competence, and the need to unify approaches to digitalization of management processes. The main criteria for choosing a learning management system are summarized. It is proven that the use of management platforms to ensure high educational productivity requires future teachers of professional education to have developed critical thinking skills, creativity, leadership qualities, adaptability, and organizational skills.